2022-RA-1171-ESGO Total vaginectomy for recurrent gynecological cancer. Experience in kazior. (20th October 2022) - Satanova, Alima; Kaydarova, Dilyara; Kukubassov, Yerlan; Bertleuov, Orynbassar; Kaldybekov, Dauren; Bolatbekova, Raikhan
Abstract : Introduction/Background: The strategy for the treatment of vaginal recurrence of gynecological cancer remains a complex clinical problem. Surgery is an effective and relatively safe strategy for these cases. Vaginectomy is one of the methods of surgical treatment of local recurrence of gynecological cancer. Although vaginectomy is considered an effective treatment for vaginal recurrence of cervical, ovarian, and endometrial cancers, only a few published reports of vaginal resections have been found, and in most cases vaginal resections have been performed by vaginal and/or open access. Several reports of laparoscopic vaginal resection for recurrence in gynecological cancer have also been found. Methodology: 7 patients were studied after vaginectomy. Results: The age of the patients ranged from 42 to 62 years (median 53 years). The duration of the operation varied from 240 to 480 minutes (median 317 min), the volume of blood loss ranged from 90 to 220 ml (median 140 ml), resection margins were negative in all cases. In 2 patients, a ureteral catheter was placed. The Foley catheter was removed after a median of 10 days (range 1 to 11 days). The length of stay of patients in the hospital ranged from 7 to 14 days (median 7 days). There were no intraoperative complications. All patients after vaginectomy are alive. Conclusion: Vaginal recurrence is the most common type of local recurrence in gynecological cancer, and there is no consensus on treatment tactics. This article is somewhat limited in terms of the number of patients, our results show the efficacy of vaginectomy in recurrent gynecological cancer.